Proposition de revenu familial garanti par intégration d’un régime bivalent d’allocations familiales à un régime de prestations sociales pour adultes - DesRochers, Gilles (L'Actualité économique, 1980)
AbstractThis paper deals with a bivalent family allowance plan comprising on the one hand a universal component and on the other, a selective component varying according to income. It will be shown that this plan will simultaneously comply with the horizontal equity objective for compensating dependants and the objective for making up family income deficiencies. This type of program must be integrated to a social welfare scheme for adults. The above-mentioned integrated scheme avoids the need for fiscal instruments such as tax credits and exemptions. Moreover, the proposed guaranteed family income scheme is preferable to a conventional guaranteed family income scheme in so far as it is as effective and generally even more effective, in making up family income deficiencies, while at the same time, insuring a horizontal equity compensation for the cost of raising children to those families whose incomes are above the poverty line. Finally, the proposed scheme is better than standard schemes because the disincentive effect on beneficiaries with regard to work effort is less.